A Mobile based peer to peer car sharing application - Nzuki, Samson Ndambuki (2020)
This research was aimed at providing a suitable solution for vehicle owners to share their vehicles when not in use as well as provide renters with a vehicle for short trips. Research indicated that private cars were idle for a majority of the time. It also aimed at solving the problems caused by an increase in private vehicles in urban areas by reducing the need to purchase additional vehicles. Information gathered from the potential users led to the formulation of requirements and implementation of a suitable solution. The mobile application and Web based backend was then developed according to the requirements and tested to ensure it worked as expected.
Printout.
Thesis ()--Oregon State University, .
Also available on the World Wide Web.
Includes bibliographical references (leaves - ).
Keywords: Database Management Systems; Vehicle Telematics; Mobile Applications